1986
DOI: 10.1007/bf00500081
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory presynaptic 5-hydroxytryptamine (5-HT) receptors on the sympathetic nerves of the human saphenous vein

Abstract: Superfused strips of the human saphenous vein preincubated with 3H-noradrenaline were used to investigate the influences of serotonin (5-HT) receptor agonists and antagonists on the electrically evoked tritium overflow. 5-HT and the preferential 5-HT1A receptor agonist 8-OH-DPAT [8-hydroxy-2-(di-n-propylamino)tetralin] concentration-dependently inhibited the evoked 3H overflow. The evoked 3H overflow was not affected by 0.1 or 1 mumol/l TVX Q 7821 (2-(4-[4-(2-pyrimidinyl)-1-piperazinyl]-butyl)-1,2-benzoisothia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1987
1987
2007
2007

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…Ketanserin in the concentration used (0.1 tIM) probably did not act on pre-or postjunctional a-receptors, since it did not affect the tritium efflux or the contraction of the preparation induced by neurogenic stimulation. This is consistent with the findings of Gothert et al (1986) for the human saphenous vein.…”
Section: Recording Of Tritium Releasesupporting
confidence: 93%
“…Ketanserin in the concentration used (0.1 tIM) probably did not act on pre-or postjunctional a-receptors, since it did not affect the tritium efflux or the contraction of the preparation induced by neurogenic stimulation. This is consistent with the findings of Gothert et al (1986) for the human saphenous vein.…”
Section: Recording Of Tritium Releasesupporting
confidence: 93%
“…In particular, inhibitory presynaptic 5-HT 1B/1D receptors have been identified on the noradrenergic axon terminals of the cardiovascular system of various species both in vitro and in vivo (Charlton et al, 1986;Göthert et al, 1986;Molderings et al, 1987Molderings et al, , 1990Molderings et al, , 1996Medhurst et al, 1997;Morá n et al, 1998;Harris et al, 2002). Therefore, one could expect that the noradrenergic nerve terminals in the CNS might also be endowed with inhibitory presynaptic 5-HT 1B/1D receptors.…”
Section: A General Aspectsmentioning
confidence: 99%
“…On the basis of the results obtained in the human saphenous vein (see Introduction; G6thert et al 1986;), our working hypothesis was that the inhibitory presynaptic 5-HT receptors in the human atrium Table 4 Comparison of the potencies of 5-HT receptor agonists in inhibiting electrically evoked tritium overflow from strips of human atrial appendages (pICs0 values from Table 2) with their affinities (pKi) reported in the literature for various cloned or native 5-HT receptors (references in parentheses). Each regression analysis is based on the comparison of the potencies and affinities of 5 to 7 compounds.…”
Section: Classification Of Presynaptic 5-ht Receptorsmentioning
confidence: 99%